Organizational changes in the coal industry foreign countries - Iryna Sapytska; Miroslaw Chudek; Iryna Maltseva (Cхід, 2017)
In the article is determined that the coal industry in many foreign countries was carried out reform, which results in the search for effective ways of taking organizational, financial, socio-economic and technical solutions.